Pemikiran Harun Ar-Rasyid tentang Pendidikan Islam dan Relevansinya dengan Pendidikan Islam Kontemporer - Khalib Gadafi; Afdhal Surya Hamid; Wandi Wandi; Ahmad Sabri; Rully Hidayatullah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Islamic education plays an important role in shaping a generation that is faithful, noble, and has a positive impact on society and Muslims in general. Harun al-Rashid, as one of the earliest thinkers, made a valuable contribution in this regard, with his concept of thought that is relevant to Islamic education today. This research aims to explain the concept of Harun Ar-Rashid's thoughts related to Islamic education and its relevance to the current context of Islamic education. The research method used is qualitative research with a literature study approach, exploring information from various sources such as literature, research reports, theses, dissertations, and electronic publications related to Harun Ar-Rashid's concept of thought on Islamic education and its relevance to the present. The results show that Harun al-Rashid's concept of Islamic education has significant inspirational value. A deep understanding of these concepts allows Islamic education to continue to develop and make a positive contribution amid the dynamics of modern times. In the midst of the complexity of the modern world, the values championed by Harun al-Rashid can be an important guideline in defining the role of Islamic education and achieving the expected noble goals.